Proses Pembentukan Citra Diri Pada Akun TikTok Husain Basyaiban ( @kadamsidik ) - Devi Ananda Prasanti, Riana; Shinta, Melisha (Jisab, 2023)
TikTok is the most popular application today. With this media, everyone can create various forms of short and long videos. Anyone can build his image in the media. One of them is Husein Basyaiban. Through the tiktok platform, Husein builds his image by spreading content that contains Islamic teachings. With the positive self-image he has built, he is able to become a da'wah content creator who is highly sought after today. With the Tiktok media, Husein can build a positive image of himself so far.